A NEW RECORD OF THE GENUS AND SPECIES TEPHROSIA NUBICA (PAPILIONACEAE) FROM IRAQ - Mousa, M. O. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was recorded a new genus and species of Iraq, Tephrosia nubica (Boiss.) Baker during the field trips in the Western Desert District, specifically in Al- Walaj valley, which cutting the Iraq- Jordan highway (75 km. West of Rutba) in winter and spring seasons of the year 2019. The species was identified depending on Flora of neighboring and nearby countries with a comprehensive morphological description as well as some drawing and photos for vegetative and floral (reproductive) parts with a distribution map of the species. Some plant samples of the species collected in the Iraqi national herbarium were deposited in numbers 60038,60039, and 60040, in addition to Anbar University herbarium in numbers 4329, 4330 and 4331 after confirming that there is no specimens of genus and species in all Iraqi herbaria.